Componentes de rendimento e qualidade de sementes de soja relacionado a aplicação de fertilizantes foliares - Machado, Fábio Ribeiro (2015)
Abstract The use of foliar fertilizers on soybean has increased in the last crops, thanks to your fast answer and low cost of use. However, the application usually is carried without a prior diagnosis of tillage, in other words, without technical criteria that justify your use. In order to give more subsidies to technicians and producers the present study aimed to study the effect of different foliar fertilizers about the yield components and soybean seed quality. The experiment was deployed in three locations, in experimental delimitation of randomized block in factorial plan 9 x2, with three replicates per treatment. The first factor relates to the treatment (T) regarding the application of different foliar fertilizers are: T1-Attestant, T2-Product A, T3- Product B; T4- Product C; T5- Product D; T6 – Product E; T7- Product F, T8- Product G e T9- Product H. The second factor refers to the two times of application of the product, one in R2 (full bloom) and the other in R5 (grain filling). The experiment was divided into two studies. In the first study, it was found the effect of foliar application of different manures on yield components and soybean yield, where the variables were evaluated, foliar nutrient content, chlorophyll content, protein content, oil content in the grain, plant height and yield components: number of pods per plant, number of grains per pod, number of grains per plant, mass of 1000 seeds and productivity. Also in this study was realized the economic analysis to verify the economic benefits the use of this technology. In study 2, was verified the performance of soybean seeds in function of application to the commercial products and application times in only 2 locations. These variables were analyzed: germination percentage; emergence in the field; speed index emergency; length of the shoot; root length; dry matter of seedlings. Although there was an increase in foliar levels of some nutrients due to products application, it was observed that had no positive results in increased productivity, possibly because the levels of nutrients in the soil and the planting fertilization were sufficient to meet crop requirements. Furthermore, the use of foliar fertilizers in the studied application times did not affect the physiological quality of soybean seeds.